ANTIMICROBIAL SENSITIVITY OF Pasteurella multocida STRAINS ISOLATED FROM PLEURITIS IN PIGS - STEPAN, ANA L. (1998)
We present the results of sensitivity tests of 98 strains of Pasteurella multocida against 8 antimicrobiaLs. The bacteria derived from pig lungs with pleuritic lesions, collected in 4 slaughterhouses in the State of Rio Grande do Sul, Brazil. The objective of the present report was to assist in the choice of antimicrobial products to control respiratory diseases in pigs. The lowest resistance rates were observed with oxolinic acid (2.1%) and ciprofloxacyn (4.2%), and the highest resistance rates with sulfazotrin (84.7%) and gentaMycin (81.7%). MI strains were sensitive at least against two drugs. We discuss the therapeutic relevante of the present resulta.